Superintendent Performance Evaluation: Current Practice and Directions for Improvement - Candoli, I. Carl. author. aut Link
XXVII, 289 p.
Keywords: Every school district needs a system of sound superintendent performance evaluation. School district superintendents are and must be accountable to their school boards, communities, faculties, and students for delivering effective educational leadership. To assure that they are evaluated fairly, competently, and functionally, superintendents need to help their school boards plan and implement evaluation systems that adhere to the evaluation standards. Superintendent Performance Evaluation outlines some of the problems and deficiencies in current evaluation practice and offers professionally-based leads for strengthening or replacing superintendent performance evaluation systems. This book focuses on the on-the-job performance of school district superintendents as they implement school board policy. The decision to focus on performance evaluation reflects the importance of this kind of evaluation in the move to raise educational standards and improve educational accountability. Boards and superintendents are advised to make superintendent performance evaluation an integral part of the district's larger system for evaluating district needs, plans, processes, and accomplishments.